2017
DOI: 10.2147/cmar.s147973
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of GATA3 promotes cell proliferation and metastasis in gastric cancer

Abstract: GATA3, a member of the GATA zinc finger transcription factor family, has been widely investigated for its role in cancer. Although a recent report has found that GATA3 is downregulated in gastric cancer (GC), the detailed mechanism of GATA3 in GC is still unknown. Here, we investigated whether GATA3 was downregulated in GC patients’ tissue samples and cell lines using quantitative real time polymerase chain reaction and Western blotting. In addition, we conducted several functional experiments to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…EMT serves key roles in cancer metastasis ( 27 ). In corroboration with previous studies ( 17 , 28 ), the present study demonstrated that GATA3 suppressed EMT in HCC cells by increasing the expression of E-cadherin and decreasing the expression of N-cadherin and vimentin. In addition, qChIP and dual luciferase reporter assays demonstrated that GATA3 transcriptionally regulated slug, thereby inhibiting EMT in HCC.…”
Section: Discussionsupporting
confidence: 93%
“…EMT serves key roles in cancer metastasis ( 27 ). In corroboration with previous studies ( 17 , 28 ), the present study demonstrated that GATA3 suppressed EMT in HCC cells by increasing the expression of E-cadherin and decreasing the expression of N-cadherin and vimentin. In addition, qChIP and dual luciferase reporter assays demonstrated that GATA3 transcriptionally regulated slug, thereby inhibiting EMT in HCC.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that GATA4 methylation was related to the clinical stage, lymph node metastasis and tumor differentiation. Interestingly, a research mainly published by Shuangqin Wei showed that the expression of GATA3 was associated with tumor size, stage and metastasis in GC, but there were no correlations between the expression of GATA3 and gender, age, pathological grade of cancer and alcohol consumption of patients [15], which was highly in line with our findings. Our work strongly demonstrated that GATA4 played a significant role in GC development and GATA4 methylation may be a potential marker for early diagnosis of GC.…”
Section: Discussionsupporting
confidence: 89%
“…It is generally recognized that GC is one of the most prevalent malignant tumors in alimentary canal and is seen as a major health problem due to its high frequency, aggressiveness and low cur e rate [14]. A recent report revealed that GATA3 could serve as an oncogene in GC development and potentially act as a novel therapeutic target [15]. But there were few researches about the mechanism of GATA4 in GC development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reverse correlation was confirmed between GATA3 and FMNL1 expressions in clinical samples. Gene silencing of GATA3 was documented in several cancers (18)(19)(20) and re-expression of GATA3 was capable of inhibiting tumor metastasis (21)(22)(23). However, the precise mechanism of FMNL1 regulation by GATA3 was not clear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%